Differential rights consciousness: Teachers' perceptions of privacy in the surveillance school. (May 2021) - Birnhack, Michael; Perry-Hazan, Lotem
Abstract: This article explores the rights consciousness of teachers as agents having a professional obligation to promote students' rights. The case study comprises Israeli teachers, whose social status is low, in the context of school CCTV surveillance. Based on 55 interviews, the findings revealed three clusters of perceptions: dismissing students' privacy as a discrete consideration in assessing school surveillance; acknowledging students' privacy as a discrete consideration; and merging students' and teachers' privacy . Almost all teachers considered their own privacy. Our conclusions focus on teachers who had differential rights consciousness and alluded to privacy justifications only when they concerned their own rights. Highlights: School CCTV surveillance affects both teachers' and students' privacy. Teachers have a professional obligation to protect their students' rights. Some teachers consider their own rights while disregarding their students' rights. This differential rights consciousness relates to teachers' low social status. Understanding differential rights consciousness may assist in shaping PD courses.